Cephalometric Appraisal of Antero-posterior Skeletal Discrepancy: An Overview (Orthodontic Journal of Nepal, 2018)
Cephalometry is one of the important diagnostic tools for assessment of jaw relationship. Sagittal jaw relationship is of utmost concern to the patients and orthodontist. Many linear and angular parameters are used for measurement of sagittal jaw discrepancies. This article reviews various AP cephalometric parameters